(untitled) (Brazilian Journal of Pharmaceutical Sciences, 2023)
Serum uric acid (UA) is a traditional biomarker in the clinical diagnosis of gout and hyperuricemia. However, serum treatment and storage are cumbersome, and wounds are susceptible to infection. Therefore, in this study, a simple and noninvasive method was developed to detect the UA in human saliva to monitor the gout. An Inertsil ODS-3 column was used for the analysis under the condition of isocratic elution with the mixed solution phosphate buffer (74 mM, pH=2.2): Methanol=98:2 (v:v) and the UV detection at 284 nm. Using salivary UA data from healthy volunteers (HVs) (n=68) and gout patients (GPs) (n=14), we examined the salivary UA difference in their content. The intra-and inter-day accuracy and precision (RSD %) were less than 2.56%, the limit of detection (LOD) of UA was 5.0 ng/mL, the mean recoveries of the corresponding compounds were 102.48%. Saliva levels of UA in HVs and GPs were 35.26±14.06 µg/mL and 91.96±23.90 µg/mL, respectively. The concentrations of salivary UA in GPs were significantly higher than those in HVs ( p < 0.001). This method was also expected to monitor the hyperuricemia and other metabolic disorders in the future.